Efficiency of foliar application of calcium sources on morphological traits, nutritional status, and vase life of two rose cultivars - Khosravi, Saeed; Tehranifar, Ali; Selahvarzi, Yahya; Khoshgoftarmanesh, Amir Hossein; Cheheltanan, Leyla (Ornamental Horticulture, 2025)
Calcium is critical in enhancing cut flower growth and quality. Despite the availability of several calcium sources, limited research has focused on identifying the most effective source of this nutrient for roses. This study aimed to determine the optimal calcium source for two rose cultivars, ‘Samurai’ and ‘Jumilia,’ by investigating the effects of foliar applications of calcium nitrate (Ca(NO3)2), calcium silicate (Ca2O4Si), and calcium amino acid chelate with glycine (Ca(Glys)2), compared to a control containing distilled water. The results demonstrated that Ca(NO3)2 significantly improved stem length in ‘Jumilia,’ while Ca2O4Si notably increased stem diameter, fresh mass, and the number of flowers. Additionally, Ca(Glys)2 was the most effective in enhancing carotenoid content. Both Ca2O4Si and Ca(NO3)2 applications elevated the levels of chlorophyll a and b and total chlorophyll, thereby enhancing photosynthetic rates. The results of this study indicate the effectiveness of Ca(NO3)2 in supplying calcium to petals, consequently increasing the membrane stability index, delaying wilting, and extending the vase life. Additionally, Ca(Glys)2 was effective in supplying calcium to the roots and phosphorus to the leaves. Ca(NO3)2 also enhanced nitrogen and copper concentrations, while Ca2O4Si increased the leaves’ potassium, iron, and manganese contents. The results indicate that using Ca(NO3)2 as a foliar spray is especially beneficial for improving cut roses’ quality and vase life.